IMPLEMENTATION OF THE THERAPEUTIC COMMUNITY REHABILITATION FOR NARCOTIC PRISONERS AT NARCOTICS PRISON CLAS II A JAKARTA - vivi sylviani biafri (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
Based on data from the National Narcotics Agency (BNN) in 2018 drug users come from among students and workers as much as 3.21 percent which is equivalent to 2,287,492 people who commit drug abuse. The impact of prison content has also increased. One of the special prisons for convicted drug cases is the Narcotics Prison Class II A Jakarta. Narcotics Prison Class II A Jakarta is a special prison that has the task of carrying out the rehabilitation of drug prisoners. Data shows drug convicts in the Special Class Narcotics Prison II A Jakarta are increasing. Data on prison occupants in 2016 were 3,168 people, in 2017 there were 2,664 people, in 2018 there were 2,416 people and in 2019 there were 2,602 people. One form of social rehabilitation carried out is the therapeutic community. Narcotics Prison Class II A Jakarta is one of the government institutions that also have an obligation to apply the values of good governance, one of which is the value of transparency. Transparency is very important to avoid undesirable things such as abuse of authority by certain parties. This research raises the issue of how the implementation of therapeutic community rehabilitation for drug prisoners in Class II A Narcotics Prison Jakarta?. This research uses a qualitative approach. This research is descriptive. Data collection techniques carried out by interview, observation, and study documentation. The research subjects were the Head of Guidance for Prisoners and Correctional Students, the supervisor of community therapeutic activities and drug prisoners. The research location is Narcotics Prison Class II A Jakarta. The purpose of this study was to determine how the implementation of therapeutic community rehabilitation in Special Narcotics Prison Class II A Jakarta. The results showed that Narcotics Lap Class II A Jakarta was not optimal in carrying out the therapeutic community rehabilitation. Few prisoners are involved in social rehabilitation activities. Besides that, the work atmosphere is less conducive. The relationship between the leadership and staff is not good, which arises a sense of mutual suspicion between staff and leaders. This is due to the non-transparency of the use of the budget for therapeutic community rehabilitation activities.